2019
DOI: 10.1021/acsabm.9b00526
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Magnetochemical Effects in Nanotherapy of Walker-256 Carcinosarcoma

Abstract: The biological and medical aspects of magnetochemical effects in nanotherapy of tumors remain poorly studied. The present paper investigates the influence of nonlinear magnetochemical effects of anisotropic magnetic nanodots on an animal tumor model. The magnetic properties and electron spin resonance spectra of magnetic nanodots and doxorubicin were investigated after mechano-magnetochemical synthesis. The results obtained from the analysis of nonlinear kinetics and survival in Walker-256 carcinosarcomabearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The influence of the magnetic and electric components of EMF converts the triplet state of lower electron energy to the excited singlet state in DOX-induced free radicals (Houston et al 2016;Jin et al 2012;Joshi et al 2005;Usselman et al 2014). The magneto-electric effects induce conformational changes in chemotherapeutic agents and, therefore, are critical for DOX intercalation into DNA (Nakata and Hopfinger 1980;Orel et al 2019a). Tumor cells are more susceptible to damage from oxidative stress than normal cells.…”
Section: •-mentioning
confidence: 99%
“…The influence of the magnetic and electric components of EMF converts the triplet state of lower electron energy to the excited singlet state in DOX-induced free radicals (Houston et al 2016;Jin et al 2012;Joshi et al 2005;Usselman et al 2014). The magneto-electric effects induce conformational changes in chemotherapeutic agents and, therefore, are critical for DOX intercalation into DNA (Nakata and Hopfinger 1980;Orel et al 2019a). Tumor cells are more susceptible to damage from oxidative stress than normal cells.…”
Section: •-mentioning
confidence: 99%
“…Further research has consistently shown that non-thermal effects induce tumor cell death. 16,20,74 External EFs can alter the competition between the singlet and the triplet radical pairs and thus change tumor redox state and growth. 75,76 The antitumor effects of MCs and EFs on Walker-256 carcinosarcoma-bearing rats were explained by the change in the electron and proton spin-dependent transport across DX-loaded Fe 3 O 4 nanoparticles and cellular biomolecules leading to ROS generation.…”
Section: Remote Control Of Redox Effectsmentioning
confidence: 99%
“…The study found a nonlinear dependence between the magnetic field intensity (200 mT, 400 mT, 600 mT), tumor redox state, growth kinetics and animal survival. 20 It is possible to hypothesize a likely mechanism by which MCs affect tumor redox state: entanglement of radical pairs under EFs. If electron spins in a radical pair are initially entangled, the behavior of one electron spin will remain affected by the other.…”
Section: Remote Control Of Redox Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since electromagnetic radiation can act on anticancer drugs with the free radical mechanism, the activity of these agents is modulated in the tumor area exposed to RIMH. [12][13][14][15] Failure of antioxidant systems to protect against elevated levels of ROS, i.e. lipid peroxidation, protein damage, leads to tumor cell death.…”
Section: Introductionmentioning
confidence: 99%